Keanekaragaman Spesies Kupu-Kupu di Taman Cibodas, Cianjur, Jawa Barat sebagai Sumber Pembelajaran Biologi : The Diversity of Butterfly Species at Cibodas Park, Cianjur, West Java as a Source of Biology Learning - Murwitaningsih, Susanti; Dharma, Agus Pambudi; Depta, Depta; Nurlaeni, Yati (SEJ (Science Education Journal), 2019)
Indonesia has many endemic butterfly species and there are about 2,000 species found in Indonesia from 17,500 species of butterflies in the world. This research was conducted for five months from January to May 2017 at Cibodas Botanical Garden of Cianjur Regency, West Java. Technique of taking data is done by butterfly captured directly by insect net in each observation point. The observation of butterflies in the three locations of Sakura Park, Guest House and Fountain at Cibodas Botanical Garden found 98 individuals from 21 species consisting of 4 families, among others Papilionidae (4 species), Nymphalidae (12 species), Pieridae ( 4 species), and Lycaenidae (1 species). At the location of Sakura Park has the highest index value, among others, the species diversity index (H '= 1.92) is moderate, the species richness index (R = 3.51), and the dominance index (C = 0.27), while the species evenness index highest at the Fountain location (E = 0.87). Students are rarely invited to visit KRC to learn directly.